EXPLORING LIBERATION: UNVEILING ITS MANIFESTATIONS IN ANITA DESAI'S NARRATIVES - Vandna Hooda Prof. (Dr) Shalini Yadav (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This paper explores the multifaceted theme of liberation in the narratives of Anita Desai, a prominent Indian author known for her nuanced portrayal of human emotions and societal constraints. Through a close examination of selected works such as Clear Light of Day, Fasting, Feasting, In Custody, and The Village by the Sea, the study delves into the diverse manifestations of liberation experienced by Desai's characters. The analysis highlights how Desai's literary craftsmanship weaves the concept of freedom into the fabric of her storytelling, presenting it as a dynamic and ongoing process rather than a singular event. In Clear Light of Day, the struggle for personal and familial emancipation is vividly depicted through the Das siblings' internal conflicts. Fasting, Feasting underscores the gender-based societal expectations faced by Uma, while In Custody presents Deven's battle between artistic aspirations and societal obligations. In The Village by the Sea, the economic struggles of characters like Lila reflect broader societal issues of poverty and opportunity. Desai's narratives portray liberation as a journey towards self-realization, autonomy, and a deeper understanding of one's place within the societal structure. This exploration of liberation is not confined to individual experiences but extends to critique the broader societal norms that constrain human potential, making Desai's work a profound commentary on the quest for personal and collective freedom.